IDENTIFIKASI KONDISI EKSISTING DAN DAMPAK SEDIMENTASI PADA SUNGAI KREO DAN KALIGARANG KOTA SEMARANG - Saputra Hasthi; Lilin Budiati; Rukuh Setiadi (saintifika, 2022)
The Garang watershed which includes the Kreo River and the Kaligarang River is an ecosystem unit that is limited by topographical separators and functions as a collector, storage, and distributor of water, nutrients, and sediment through the river's hydrological system. Garang watershed plays an important role in achieving Sustainable Development Goals (SDGs) 6 related to clean water, namely supplying drinking water raw materials in the city of Semarang experiencing environmental damage due to sedimentation common in river systems in Indonesia. Sedimentation occurs due to the deposition of fragmental material by water caused by erosion. Erosion consists of three phases, namely the release of soil particles and then transport by erosion agents (wind and water). Sediment deposition occurs which is influenced by natural and anthropogenic factors. The impact of sedimentation causes siltation which affects the decreasing capacity of river flow and decreases river water quality. This study aims to identify and analyze the existing conditions of the Kreo River and Kaligarang River related to the impact of sedimentation with qualitative descriptive methods and literature studies of previous studies. The Kreo River and Kaligarang River experience sedimentation due to suspended solids in the form of soil and sand mixed with household waste, resulting in decreased river flow and water quality. This is in line with the results of literature studies from previous studies, in 2008 sedimentation in the Kaligarang River was 124.944.13 tons/year with an erosion rate of 1,064.260.08 tons/ha/year. In 2009-2014 sedimentation in the Kreo River increased from 2,781 to 4,083 tons/year with an erosion rate of 17,827 - 26,171 tons. It can be concluded that the Kaligarang River and the Kreo River are currently experiencing increased sedimentation, so they are threatened with silting and damage to the river's natural functions.